(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
The present work was developed in the deboning area of a meat products company, located in the city of Barquisimeto, Lara state, Venezuela, with the objective of evaluating the ergonomics of its workstations, due to musculoskeletal illnesses reported in some workers. In this sense, the data collection and analysis techniques used were: Direct observation, interviews, process flow chart, checklist and cause-effect diagrams. The level of dysergonomic risk was assessed using the Rapid Entire Body Assessment method (REBA), determining that the major causes of the mentioned pathologies were repetitive movements, manual work adopting forced postures, lack of rest periods, inadequate height of the work stations, and no mechanicals equipments for specific tasks, all this resulting in a high risk level for the employees. Consequently, in order to reduce these risks, a set of measures were recommended for its immediated application. Among these measures were: the installations of anti-fatigue carpets, implementation of resting periods, rotating schedules, redesign of workstations according to the anthropometric measures of the workers, training of personnel and installation of mechanical equipment to perform certain tasks.